Evaluation of a static mixer as a new microfluidic method for liposome formulation - Ota, Aoba; Mochizuki, Ayaka; Sou, Keitaro; Takeoka, Shinji (Frontiers in Bioengineering and Biotechnology, 2023)
Microfluidic formulation of liposomes has been extensively studied as a potential replacement for batch methods, which struggle with problems in scalability and difficulty in modulating conditions. Although microfluidic devices are considered to be able to combat these issues, an adequate replacement method has yet to be established. This paper examines the potential of a static mixer (SM) by comparing the encapsulation efficiency, loading, lamellarity, and user-friendliness with a commonly used microfluidic device, a staggered herringbone micromixer (SHM). In both devices, it was found that as the initial lipid concentration increased, the particle size increased; however, the overall particle size was seen to be significantly larger in the liposomes prepared with SM. PDI remained significantly smaller in SM, however, signifying that better control of the particle size was accomplished in SM. In addition, the encapsulation efficiency was slightly smaller in SM compared to SHM, and in both devices, the values increased as the initial lipid concentration increased. The increase in encapsulation efficiencies was significantly smaller than that of the theoretical encapsulation efficiency, and this was found to be due to the increase in lamellarity as the initial lipid concentration increased. In terms of user-friendliness, SM demonstrated significant advantages. The mixing elements could be taken out from the device, allowing for thorough cleaning of the element and device before and after experiments and ensuring experiments are conducted at virgin state in every round. Consequently, it was found that SM not only can produce uniformly distributed liposomes but has the potential to become a more practical method for liposome formulation with modifications in the mixing elements.